Methodology of scientific research in neurobiological rehabilitation - Glück, Joanna; Rymarczyk, Barbara; Rogala, Barbara (European Journal of Clinical and Experimental Medicine, 2008)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Scientific researches may be performed by physicians in parallel to their medical practice, broadening their minds and the general knowledge. The authors described the most often types of research and clinical studies, the rules of their designs, protocols and data analysis. Some regulatory and ethical aspects and good clinical practice rules were discussed, as well. Moreover, the information on journal ranking lists, impact factor and immediacy index ‘was covered and some tips on manuscript preparations were given.